An Evaluation of Giving the Jamaican Government School Meal to a Class of Children - Grantham-McGregor, Sally M.; Powell, Christine; Elston, M. (My University, 1983)
This study evaluated the effects of giving the standard Jamaican government school meal to a class of schoolchildren. Unlike any other school feeding studies, this project was carefully controlled and carried out with under-nourished children who had low levels of school attendance and achievement. In spite of this, no improvement was found in the children’s nutritional status as reflected by weight for age. However small benefits were found in attendance and school achievements. These findings remained when sex, age, improvements over the previous term and the effects of “benevolent attention” were taken into account.
Keywords: Academic achievement